Peran Teori Sosial Émile Durkheim Dalam Pengembangan Pendidikan Agama Islam (Perspektif Solidaritas Sosial Dan Integrasi Masyarakat) - Fathoni, Tamrin; Moh. Hazim Ahrori; Wahyuni, Fitri; Samsudin, Samsudin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of this study is to analyze the role of Durkheim's social solidarity theory in the development of Islamic religious education in the context of social integration of Muslim society. This study uses a library method to analyze the role of Émile Durkheim's social theory in the development of Islamic religious education, focusing on the theory of social solidarity and its application. The literature used includes Durkheim's works as well as recent articles and research related to the relationship between Islamic religious education and social solidarity. By reviewing various references, this study aims to deepen understanding of the application of Durkheim's theory in the context of Islamic religious education in society. Islamic religious education has an important role in forming social solidarity through values ​​such as ukhuwah, ta'awun, and social justice. Durkheim's principle of social solidarity which emphasizes shared values ​​is very relevant to be applied in Islamic religious education. By teaching these values, Islamic religious education can strengthen social integration and create a more harmonious and just society.